Spinel magnesium ferrite (MgFe2O4): a glycine-assisted colloidal combustion and its potentiality in gas-sensing application - Nadargi, Digambar; Umar, Ahmad; Nadargi, Jyoti; Patil, Jayvant; Mulla, Imtiaz; Akbar, Sheikh; Suryavanshi, Sharad (Chemosensors, 2022)
Herein, we describe the facile synthesis of spinel MgFe2O4 ferrite and its potential use as a gas sensor using a straightforward and reliable sol-gel approach, i.e., the glycine-assisted auto-combustion route. The novelty in obtaining the sensing material via the auto-combustion route is its inherent simplicity and capability to produce the material at an industry scale. The said cost-effective process makes use of simple metal salts (Mg and Fe-nitrates) and glycine in an aqueous solution, which leads to the formation of spinel MgFe2O4 ferrite. A single-phase crystallinity with crystallite sizes ranging between 36 and 41 nm was observed for the synthesized materials using the X-ray diffraction (XRD) technique. The porous morphologies of the synthesized materials caused by auto-ignition during the combustion process were validated by the microscopic investigations. The EDS analysis confirmed the constituted elements such as Mg, Fe, and O, without any impurity peaks. The gas-sensing ability of the synthesized ferrites was examined to detect various reducing gases such as LPG, ethanol, acetone, and ammonia. The ferrite showed the highest response (>80%) toward LPG with the response and recovery times of 15 s and 23 s, respectively. Though the sensor responded low toward ammonia (similar to 30%), its response and recovery times were very quick, i.e., 7 s and 9 s, respectively. The present investigation revealed that the synthesized ferrite materials are good candidates for fabricating high-performance sensors for reducing gases in real-world applications.
Keywords: Gas sensors; glycine combustion; MgFe2O4; reducing gases

Gas sensors and factors influencing sensing mechanism with a special focus on MOS sensors - Nadargi, Digambar Y. Y.; Umar, Ahmad; Nadargi, Jyoti D. D.; Lokare, Smita A. A.; Akbar, Sheikh; Mulla, Imtiaz S. S.; Suryavanshi, Sharad S. S.; Bhandari, Nagesh L. L.; Chaskar, Manohar G. G. (Journal of Materials Science, 2023)
Industrialization and its progress are very important for the economy and to move towards prosperity, stimulating innovation and creating jobs. Nonetheless, industrialization has negative impacts, if not done judiciously, such as pollution, increased greenhouse gas emissions, and global warming. Therefore, amenity-with-security is of fundamental significance in a new and dynamic lifestyle. A gas sensor is one of the crucial devices for monitoring and subsequently preserving the clean atmosphere among a number of other safety technologies. In-depth assessments of gas sensors and their necessity in the environment (air) pollution are provided in the current review. With a special emphasis on metal oxide semiconductor (MOS)-based gas sensors, the review includes a thorough study of gas sensors and the factors relating to sensing mechanisms. It not only describes the basic concepts and brief history of gas sensors, but also highlights the schemes responsible for improving the gas sensing properties and state-of-art literature review. These schemes include (1) surface engineering/morphological tuning and (2) bulk and surface doping. To keep scientific rigour and in-depth analyses, this review focuses on these two schemes only. In the doping area, the emphasis is given on graphene loading, decorated with nanoparticles of noble metals, spillover mechanism, and heterojunction (p-n, n-n, and p-p) formation. The conclusion summarizes the most optimized MOS gas sensors with enhanced gas sensing capabilities. The emphasis is given to formulate the article in such a way that it will be useful for the beginners who wish to explore the gas sensor research field, as well as to the established researchers to further improve the sensing capabilities of MOS gas sensors.